2011
DOI: 10.1007/s10396-011-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

Inter-twin contact in a case of monochorionic diamniotic twins with acrania of one twin fetus at 10–13 weeks’ gestation

Abstract: Anencephaly can be reliably diagnosed using ultrasound late in the first trimester of pregnancy [1]. The prevalence of anencephaly in twins is higher than that in singleton pregnancies, and the prevalence of discordance in anencephaly in monochorionic twins is higher than that in dichorionic twins [2].There have been only two reports on conventional twodimensional (2D) sonographic assessment of fetal behavior in twins discordant because of anencephaly after 20 weeks of gestation [3,4]. However, there has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…25). 27 Notably, the frequencies of about half of contacts at 12-13 weeks were low. Hata et al 4 were the first to document reactionary movement in twin fetuses using conventional 3D ultrasound at 25 weeks and 1 day of pregnancy.…”
Section: Inter-twin Contact and Intra-pair Stimulationmentioning
confidence: 99%
“…25). 27 Notably, the frequencies of about half of contacts at 12-13 weeks were low. Hata et al 4 were the first to document reactionary movement in twin fetuses using conventional 3D ultrasound at 25 weeks and 1 day of pregnancy.…”
Section: Inter-twin Contact and Intra-pair Stimulationmentioning
confidence: 99%
“…Our twin study showed that the difference in the frequency of the type of inter‐twin contact at 10–13 GW might be due to early fetal neuromuscular development and differentiation of the neuromuscular system . Moreover, a decreased number of inter‐twin contacts was noted in a case of MD twins with acrania of one of them at 10–13 GW …”
Section: Twin Studiesmentioning
confidence: 99%
“…27 Moreover, a decreased number of inter-twin contacts was noted in a case of MD twins with acrania of one of them at 10-13 GW. 28 Castiello et al 29 studied kinematic profiles of movements in twin fetuses using 4-D ultrasound at 14 and 18 GW. These authors concluded that the performance of movements towards the co-twin was not accidental, and twin fetuses executed movements specifically aimed at the co-twin already starting from 14 GW.…”
Section: Twin Studiesmentioning
confidence: 99%
“…The more active twin in each pair showed a close correlation with prenatal intertwin differences in activity. These authors suggested that differences in activity in each pregnancy even before the The quartile ranges at 12 to 13 weeks were adopted from normal monochorionic diamniotic (MD) twins in our previous investigation 46 (Courtesy: Reprinted with permission from Hata T et al) 51 emergence of fetal behavioral patterns were followed by differences in temperament postnatally.…”
Section: Intertwin Contact and Intrapair Stimulationmentioning
confidence: 99%
“…Hata et al 51 were the first to report on 4D sonographic assessment of intertwin contact in a case of MD twin with an acrania of one twin fetus late in the first trimester (Fig. 21).…”
Section: Intertwin Contact and Intrapair Stimulationmentioning
confidence: 99%